HUBUNGAN STATUS GIZI DAN BERAT LAHIR DENGAN PERKEMBANGAN ANAK USIA 30-35 BULAN - Suwito, Sri Juanita; Sumarah, Sumarah; Estiwidani, Dwiana (Jurnal Kesehatan Ibu dan Anak, 2014)
The prevalence of undernourished toddler nationally is 10 %, while still at DIY 10,28 %. Figures for malnutrition in the city increased from 2010 (1,01 %) to year 2011 (1,35 %) and a decrease in the prevalence of LBW from 2010 (5,51 %) to the year 2012 (4,92 %). Poor nutritional status third highest guiler in Puskesmas Mantrijeron of 1,87 % and followed the high prevalence of LBW amounted to 6,42 %. Results of the initial survey found 0,8 % severely interruption of development and some have a history of abnormal birth weight. Objective to know the relationship of nutritional status and birth weight with child development ages 30-35 months. Analytical research methods with crossectional approach. Population of 75 children age 30-35 months. A sample of 42 subject taken with accidental sampling techniques. Implementation at the Posyandu. Technique of data analysis using Chi-Square. Types of nominal scale. Result : 40 subject (95,2 %) had normal nutritional status with normal birth weight by as much as 38 subject (90,5 %) and the development of appropriate age by as much as 37 subject (88,1 %). The majority of the subjects who have normal nutritional status and birth weight have the development of appropriate age. There is no relationship of nutritional status with child development with ?-value of 0,60. There is a relationship of birth weight with child development with ?-value 0,01 and contingency coefficient of 0.36 category clinging low levels. Conclusion : there is a relationship of birth weight with child development and there is no relationship of nutritional status with child development ages 30-35 months in Puskesmas Mantrijeron by 2013.